Aktivitas Antibakteri Asap Cair yang Diproduksi Dari Bermacam-Macam Limbah Pertanian - Purnama Darmadji (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1996)
Liquid smokes were produced from several dry agricultural wastes by pyrolysis at 400°C followed by condensation. The condensates were subjected to investigation of antimicrobial activity against some spoilage and pathogenic bacterias normally occuring on meat. The liquid smokes contained phenol and carbonyl ranging from 2.11 - 3.50% and 9.3 -17.8%, respectively, and had pH values ranging from 2.8 - 3.1. The antimicrobial activities were high against Staphylococcus aureus, Bacillus subtilis, Escherichia cold, Pseudomonas fluorescens and naturally occuring meat flora.